Preparation and biological evaluation of conformationally constrained BACE1 inhibitors. Issue 13 (1st July 2015) - Winneroski, Leonard L.; Schiffler, Matthew A.; Erickson, Jon A.; May, Patrick C.; Monk, Scott A.; Timm, David E.; Audia, James E.; Beck, James P.; Boggs, Leonard N.; Borders, Anthony R.; Boyer, Robert D.; Brier, Richard A.; et al.
Graphical abstract: Abstract: The BACE1 enzyme is a key target for Alzheimer's disease. During our BACE1 research efforts, fragment screening revealed that bicyclic thiazine3 had low millimolar activity against BACE1. Analysis of the co-crystal structure of3 suggested that potency could be increased through extension toward the S3 pocket and through conformational constraint of the thiazine core. Pursuit of S3-binding groups produced low micromolar inhibitor6, which informed the S3-design for constrained analogs7 and8, themselves prepared via independent, multi-step synthetic routes. Biological characterization of BACE inhibitors6 –8 is described.